Association of Surgical Resident Wellness With Medical Errors and Patient Outcomes. Issue 2 (August 2021) - Hewitt, Daniel Brock; Ellis, Ryan J.; Chung, Jeanette W.; Cheung, Elaine O.; Moskowitz, Judith T.; Huang, Reiping; Merkow, Ryan P.; Yang, Anthony D.; Hu, Yue-Yung; Cohen, Mark E.; Ko, Clifford Y.; Hoyt, David B.; et al.
Abstract : Objectives: The aims of this study were to: (1) measure the prevalence of self-reported medical error among general surgery trainees, (2) assess the association between general surgery resident wellness (ie, burnout and poor psychiatric well-being) and self-reported medical error, and (3) examine the association between program-level wellness and objectively measured patient outcomes. Summary of Background Data: Poor wellness is prevalent among surgical trainees but the impact on medical error and objective patient outcomes (eg, morbidity or mortality) is unclear as existing studies are limited to physician and patient self-report of events and errors, small cohorts, or examine few outcomes. Methods: A cross-sectional survey was administered immediately following the January 2017 American Board of Surgery In-training Examination to clinically active general surgery residents to assess resident wellness and self-reported error. Postoperative patient outcomes were ascertained using a validated national clinical data registry. Associations were examined using multivariable logistic regression models. Results: Over a 6-month period, 22.5% of residents reported committing a near miss medical error, and 6.9% reported committing a harmful medical error. Residents were more likely to report a harmful medical error if they reported frequent burnout symptoms [odds ratio 2.71 (95% confidence interval 2.16–3.41)] or poor psychiatric well-being [odds ratio 2.36 (95% confidence interval 1.92–2.90)]. However, there were no significant associations between program-level resident wellness and any of the independently, objectively measured postoperative American College of Surgeons National Surgical Quality improvement Program outcomes examined. Conclusions: Although surgical residents with poor wellness were more likely to self-report a harmful medical error, there was not a higher rate of objectively reported outcomes for surgical patients treated at hospitals with higher rates of burnout or poor psychiatric well-being. Abstract : Supplemental Digital Content is available in the text